Competitive Salt Precipitation/Dissolution During Free‐Water Reduction in Water‐in‐Salt Electrolyte. Issue 37 (22nd June 2020) - Bouchal, Roza; Li, Zhujie; Bongu, Chandra; Le Vot, Steven; Berthelot, Romain; Rotenberg, Benjamin; Favier, Frederic; Freunberger, Stefan A.; Salanne, Mathieu; Fontaine, Olivier
Abstract: Water‐in‐salt electrolytes based on highly concentrated bis(trifluoromethyl)sulfonimide (TFSI) promise aqueous electrolytes with stabilities nearing 3 V. However, especially with an electrode approaching the cathodic (reductive) stability, cycling stability is insufficient. While stability critically relies on a solid electrolyte interphase (SEI), the mechanism behind the cathodic stability limit remains unclear. Now, two distinct reduction potentials are revealed for the chemical environments of free and bound water and that both contribute to SEI formation. Free water is reduced about 1 V above bound water in a hydrogen evolution reaction (HER) and is responsible for SEI formation via reactive intermediates of the HER; concurrent LiTFSI precipitation/dissolution establishes a dynamic interface. The free‐water population emerges, therefore, as the handle to extend the cathodic limit of aqueous electrolytes and the battery cycling stability. Abstract : Water‐in‐salt electrolytes have received particular attention for their electrochemical stability properties. It is now shown that water reduction is always present from the first measured currents, and that associated with this water reduction, LiTFSI precipitation occurs.